Sustainability Assessment of Rural Water Service Delivery Models : Findings of a Multi-Country Review - World Bank Group (World Bank, Washington, DC, 2017)
With 2.1 billion people – mostly in rural areas – lacking safely managed drinking water and reported low rural water supply functionality rates, the Sustainable Development Goals pose a triple challenge: to reach unserved mostly rural population groups, to raise service levels, and to sustain existing and future services. This assessment uses a multi-country case study approach to identify good practices and challenges toward building sector capacity and strengthening sustainable service delivery models for rural areas. Recognizing the limitations of the Demand Responsive Approach, the emergence of various management models, the identified need for ongoing support to rural service providers, and the critical role of enabling institutions and policies beyond the community-level, the added value of this assessment lies in: i)the development of a comprehensive analytical framework that can be used to analyze and operationalize a more sustainable service delivery approach for rural water supply; ii) the rich set of cases and good practices from the 16 countries informing the global body of "knowledge in implementation," and iii) the formulation of recommendations and policy directions to improve the sustainability of services depending on sector development stage. Policy recommendations are centered around five areas: institutional capacity, financing, asset management, water resources management, and monitoring and regulatory oversight.